Kebutuhan Air Sektoral untuk Pengembangan DAS - M. Yanuar J. Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2007)
There is a requirement for providing water supply sufficiently for the major customer sectors including residential areas in watershed development and planning. However, the sectoral water demand has also been changing over time. More over, continuing population growth and the job opportunity has resulted in increasing water demand within dynamic manner in residential areas. This study aims to develop water demand model in water management for watershed development planning. Actual water allocations for the experimental watershed, in Banten Province, were used for the model calibration process. The established model was used for predicting the amount of water demand in the future. The advantage of this model is for guiding the local government in providing water for the community.ABSTRAKDalam kegiatan pengembangan daerah aliran sungai (DAS), diperlukan kebutuhan air untuk semua sektor yang akan dikembangkan di wilayah tersebut. Perkembangan wilayah dan komunitas selama kurun waktu perencanaan juga akan mempengaruhi nilai total jumlah kebutuhan air untuk wilayah DAS. Hal ini disebabkan adanya perkembangan populasi dan pergerakan kesempatan kerja yang tersedia dari sektor satu ke sektor yang lain. Penelitian ini bertujuan mengembangkan sebuah pendekatan untuk menghitung kebutuhan air sektoral dalam suatu wilayah DAS. Kebutuhan air untuk suatu sampel DAS digunakan untuk melakukan kalibrasi. Manfaat pendekatan kebutuhan air sektoral adalah untuk memprediksi nilai total kebutuhan air wilayah dengan memperhatikan sektor-sektor yang diprioritaskan maupun perkembangan penduduknya. Hal ini dapat membantu pemerintah dalam merencanakan pembangunan untuk suatu komunitas di wilayah tertentu.